P2X7 Receptor–Mediated Inflammation in Cardiovascular Disease - Zhou, Junteng; Zhou, Zhichao; Liu, Xiaojing; Yin, Hai-Yan; Tang, Yong; Cao, Xin (Frontiers in Pharmacology, 2021)
Purinergic P2X7 receptor, a non-selective cation channel, is highly expressed at immune cells as well as cardiac smooth muscle cells and endothelial cells. Its activation exhibits to mediate nucleotide-binding domain (NOD) like receptor protein 3 (NLRP3) inflammasome activation, result in release of interleukin-1 beta (IL-1β). interleukin-18 (IL-18) and pyroptosis, and thus trigger inflammatory response. These pathological mechanisms lead to the deterioration of various cardiovascular diseases including atherosclerosis, arrhythmia, myocardial infarction, pulmonary vascular remodeling, and cardiac fibrosis. All these worsening cardiac phenotypes are proven to be attenuated after the P2X7 receptor inhibition in experimental studies. The present review aims to summarize key aspects of P2X7 receptor-mediated inflammation and pyroptosis in cardiovascular diseases. The main focus is on the evidence addressing the involvement of the P2X7 receptor in the inflammatory responses to the occurrence and development of cardiovascular disease and the therapeutic interventions.